The Effectiveness of the Five-Tier Multiple Choice Diagnostic Test Instrument in Measuring Misconceptions and Science Literacy in The Acids Bases Topic in Senior High Schools - Rendika Adisman; Maria Erna; Dedi Futra; Sabarno Dwirianto (MASI Mandiri Edukasi, 2026)
Misconceptions in acid-base chemistry are prevalent and persistent, yet conventional assessments cannot distinguish them from a lack of knowledge or guessing, leaving teachers without actionable diagnostic data. This study aimed to develop, validate, and evaluate a five-tier multiple-choice digital diagnostic e-instrument (eFTMCDI) for acid-base chemistry in Indonesian secondary schools. Using the 4D development model, six experts validated a 30-item draft across two rounds; preliminary psychometric testing involved 30 students, and dissemination was conducted with 61 students across two schools with contrasting academic profiles. The final 23-item instrument demonstrated very high reliability (Cronbach's α = 0.850), 93.3% of items at moderate difficulty, and Very Valid expert ratings across all six dimensions, with practicality confirmed as Very Good by students (96.25%) and teachers (97.75%). Field testing revealed distinct conceptual profiles between schools: the regular-track school was dominated by No Understanding (56.5%). In comparison, the elite-track school exhibited a notably higher Misconception rate (24.8% vs. 13.6%) — a pattern detectable only through the dual confidence-rating architecture of Tiers 2 and 4. Scientific literacy scores differed significantly between schools (84.12 vs. 62.45; p < 0.001). The eFTMCDI may provide a potential tool to support evidence-based formative assessment by simultaneously profiling misconception typology and scientific literacy within a single digital session.